Improved outcomes of feeding low birth weight infants with predominantly raw human milk versus donor banked milk and formula. (2nd April 2016) - Dritsakou, Kalliopi; Liosis, Georgios; Valsami, Georgia; Polychronopoulos, Evangelos; Skouroliakou, Maria
Abstract: Objectives : To investigate the benefits of treating low birth weight infants predominantly with mother's own raw milk and early initiation of breastfeeding (raw human milk/breast-fed infants), in comparison to feeding only with donor banked milk (until the third week of life) and afterwards a preterm formula until hospital discharge (donor banked/formula-fed infants). Methods : One hundred and ninety-two predominantly raw human milk-fed infants (70% of raw and 30% of donor milk) were matched to 192 donor/formula-fed ones (on 1:1 ratio). Aggressive nutrition policy and targeted fortification of human milk were implemented in both groups. Results : The two groups show similar demographic and perinatal characteristics. Predominantly raw milk-fed infants regained earlier their birth weight, suffered less episodes of feeding intolerance and presented a higher body length and head circumference at discharge ( p < 0.001). Those treated mainly with their mothers' milk were able to initiate breastfeeding almost 2 weeks earlier compared to those fed with donor milk who achieved to be bottle-fed later on post-conceptual age ( p < 0.001). Infants being breastfed until the 8th month of life conducted less visits for a viral infection to a pediatrician compared to those in the other group ( p < 0.001). Conclusions : Feeding predominantly with mother's raw milk seems to result in optimal neonatal outcomes.